(untitled) (Sciences & Technology. A, exactes sciences, 2017)
Low energy neutrinos can be used to probe the Earth’s density from the study of the Earth’s matter effects on their oscillation. In this work, we will show how this can be achieved with neutrinos coming from a future Galactic Supernova explosion ( ), using an analytic formula that describes the Earth’s matter effects on their oscillation. We will focus, in this study, on the linear case where neutrinos travel short distances ( ) through the Earth, showing how a Tomogram of the Earth (a 2D image from a 3D body) can be created just by making use of the information obtained from the observation of the Earth’s matter effects, which is the case for specific choices of the neutrino oscillation parameters and the neutrino mass schemes. In our work, we will treat the case where the neutrino oscillations are explained by the large mixing angle solution to the solar neutrino problem (LMA), combined with the normal mass hierarchy.